Social appearance anxiety (SAA), fear of missing out (FOMO), and neuroticism as predictors of social media addiction (SMA) among undergraduate students in Malaysia - Goh, Jaclyn Shi Xin; Chan, Janice Cheng Yee; Koh, Qin Xuan (2024)
The phenomenon of social media dependency is on an upward trajectory among collegiate populations, a trend that can be ascribed to the advent of new technologies, potentially leading to a spectrum of detrimental psychological impacts on users who engage excessively. The current study sought to explore the roles of social appearance anxiety, the fear of missing out, and neuroticism as potential determinants of social media addiction within a cohort of undergraduate students in Malaysia. By employing a quantitative, descriptive methodology, the study utilized purposive sampling within a cross-sectional framework. Participants included 161 undergraduates ranging from 18 to 26 years of age (M = 20.37; SD = 1.49), with a female representation of 61.5% (n = 99) and a male representation of 37.3% (n = 60), encompassing Malay, Chinese, and Indian ethnicities. Data collection was facilitated through online platforms, with the survey constructed via Qualtrics and data analysis conducted using IBM SPSS version 23. Instruments including the Social Appearance Anxiety Scale (SAAS), Fear of Missing Out Scale (FoMOs), Big Five Inventory (BFI), and Bergen Social Media Addiction Scale (BSMAS) were employed. A multiple linear regression analysis was executed to ascertain the predictive effect of social appearance anxiety, fear of missing out and neuroticism on social media addiction. Outcomes revealed that social appearance anxiety and fear of missing out served as positive predictors of social media addiction among undergraduate students in Malaysia, whereas neuroticism served as a negative predictor. These insights are poised to enrich subsequent research endeavors and inform relevant entities in a more holistic examination and discussions on social media addiction issues. The study highlighted the importance of implementing targeted interventions and public awareness initiatives to address excessive digital usage. It also emphasized the need for collaborative efforts between mental health professionals and policymakers to reduce its adverse effects on mental health.